2006
DOI: 10.1021/nl052316g
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of a Gold Nanoparticle Wire Assembled Using Mg2+-Dependent RNA−RNA Interactions

Abstract: Magnesium-ion-mediated RNA-RNA loop-receptor interactions, in conjunction with gold nanoparticles derivatized with DNA, have been used to make self-assembled nanowires. A wire located between lithographically fabricated nanoelectrodes is demonstrated that exhibits activated conduction by electron hopping at temperatures in the 150-300 K range. These techniques have the ability to link particles between devices and in the future may be used to assemble practical circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…Bates et al 17 fabricated a nanowire made of gold spheres 15 nm in diameter, which are linked to each other and to electrodes by biomolecules such as DNAs and RNAs. They found that the transport in the nanowire is affected by grain vibrations.…”
Section: Discussionmentioning
confidence: 99%
“…Bates et al 17 fabricated a nanowire made of gold spheres 15 nm in diameter, which are linked to each other and to electrodes by biomolecules such as DNAs and RNAs. They found that the transport in the nanowire is affected by grain vibrations.…”
Section: Discussionmentioning
confidence: 99%
“…non-RNA nature (proteins, small targeting molecules, gold NP, etc) [93][94][95][96], discussed in detail in Functionalization and Modification, below. The second class encompasses tectonic units that can be split into structural motifs and interacting motifs possessing discrete secondary and tertiary structures which can be combined to rationally produce self-assembling nanoparticles with predictable, multi-dimensional structures in vivo or in vitro.…”
Section: Rna Architectonic Approach (Tectorna)mentioning
confidence: 99%
“…This combination of specific, programmable supramolecular structures with diverse functional units in a single, entirely RNA compound, allows precise positioning of different functional modules in three-dimensional space. This, for example, can provide an avenue to address the vital problems of stability, targeting, and multivalency in nanomedicine [95,102,103,107], and can form the basis of preprogrammed arrays [43], mediate the growth and distribution of other NPs [94,108], or form patterned scaffolds for tissue engineering or other applications [47].…”
Section: Rna Architectonic Approach (Tectorna)mentioning
confidence: 99%
“…(Fig. 1) Such a system might be realized by attaching the particle to the electrodes with bio-molecules such as RNA or DNA 9 . The metal island is assumed to be a sphere that supports a variety of acoustic phonon modes (Appendix A).…”
Section: Introductionmentioning
confidence: 99%